Maximizing Economic Growth in Indonesia: A Model-Based Exploration of Optimal Tax Ratios - Yossinomita, Yossinomita; Haryadi, Haryadi; Nainggolan, Saidin; Zulfanetti, Zulfanetti (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
The tax ratio is often used as an indicator to compare tax revenue to gross domestic product (GDP). It offers valuable insights into the overall tax burden on the economy, aiding policymakers and economists in comprehending the extent of taxes in relation to the economic scale. This study examines the tax ratio on economic growth and identifies the ideal tax ratio that could be implemented to achieve optimal economic growth in Indonesia. Applying ordinary least squares (OLS) regression which passes classical hypothesis testing, this study spans a research period of 39 years, covering the years 1983 to 2021. The regression estimation results show that the relationship between the tax ratio and economic growth is non-linear, with a t-statistic value of -2.952949, revealing a high significance level at a probability of 0.0057. Additionally, the t-statistic for the squared tax ratio is 2.540621, demonstrating a significant probability of 0.0158. This empirical evidence suggests that in the early stages, an increase in the tax ratio has a contractionary effect on economic growth., However, if it has reached a certain tax ratio value of 15.29%, a further rise in the tax ratio becomes expansionary, positively influencing economic growth. The tax ratio value of 15.29% is the ideal for creating optimal economic growth in Indonesia. The regression estimation results of this study prove that the government should not be concerned about the increasing of the tax ratio, because it will actually stimulate Indonesia's economic growth. Apart from that, the shape of the Laffer curve, illustrating the relationship between tax revenues and Indonesia's economic growth differs notably from the typical inverted